Synthetic ligustrazine based cyclohexanone and oxime analogs as Anti-Trypanosoma and Anti-Leishmanial agents (Brazilian Journal of Pharmaceutical Sciences, 2022)
In the present study a series of 34 synthetic ligustrazine-containing α, β-Unsaturated carbonyl-based compounds and oximes, recognized as anticancer compounds were assessed against protozoa of the Trypanosoma and Leishmania species. Ligustrazine, chemically known as tetramethylpyrazine (TMP), was selected as the core moiety for the synthesis of α, β-Unsaturated carbonyl-based compounds and these compounds were selected as precursors for the synthesis of new oximes. Some derivates, including 5f and 6i, showed multiple activities against all tested strains. In particular compounds 5f and 8o are the most potent and they are, therefore, potential candidates for trypanosomiasis and leishmaniasis.